2019
DOI: 10.1093/ecco-jcc/jjz116
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Evaluation of Allogeneic Bone Marrow-derived Mesenchymal Stromal Cell Therapy for Crohn’s Disease Perianal Fistulas

Abstract: Background and Aims The long-term safety and efficacy of allogeneic bone marrow-derived mesenchymal stromal cell [bmMSC] therapy in perianal Crohn’s disease [CD] fistulas is unknown. We aimed to provide a 4-year clinical evaluation of allogeneic bmMSC treatment of perianal CD fistulas. Methods A double-blind dose-finding study for local bmMSC therapy in 21 patients with refractory perianal fistulising Crohn’s disease was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 24 publications
1
90
0
2
Order By: Relevance
“…ADSCs in HA hydrogel have also reported to significantly improve disc function in patients with chronic discogenic lower back pain (220). Similar positive findings have also been reported regarding the use of local administration for tissue repair responses, including the closure of fistulas in Crohn's disease patients with, as previously reported, no negative side effects of MSC treatment (221). Intramuscular injection of allogenic MSCs have also been safely employed for the treatment of digital ulcers in systemic sclerosis autoimmune disease(222).…”
Section: Clinical Usage Of Mscs In the Treatment Of Vf Scarringsupporting
confidence: 61%
See 1 more Smart Citation
“…ADSCs in HA hydrogel have also reported to significantly improve disc function in patients with chronic discogenic lower back pain (220). Similar positive findings have also been reported regarding the use of local administration for tissue repair responses, including the closure of fistulas in Crohn's disease patients with, as previously reported, no negative side effects of MSC treatment (221). Intramuscular injection of allogenic MSCs have also been safely employed for the treatment of digital ulcers in systemic sclerosis autoimmune disease(222).…”
Section: Clinical Usage Of Mscs In the Treatment Of Vf Scarringsupporting
confidence: 61%
“…MSCs have been shown in multiple organ systems to play a pivotal role in tissue homeostasis and repair (219)(220)(221)(222)(266)(267)(268)(269).Their ability to home to sites of injury and modulate the activity of both immune cells and resident stromal fibroblasts has established fundamental reparative roles for MSCs in all phases of the healing cascade (142,270,271).…”
Section: Msc Modulation Of Acute Injury Responsementioning
confidence: 99%
“…The most success was found in cohort 2 as all fistulas were closed 4 years after bonemarrow MSC therapy was locally applied. Success was also found in cohort 1 and 3 as 63% and 43% of the fistulas were closed upon reevaluation [42]. A phase II pilot clinical study by Liang et al, treated 9 individuals suffering from CD with allogeneic BM-MSC transplantation.…”
Section: Allogeneic Bone-marrow Mscmentioning
confidence: 97%
“…In the early 1990s, Crohn's disease patients were reported to experience relief from their inflammatory bowel disease following infusion of HSCs, and subsequently, HSC transplantation has been developed for refractory patients that do not respond to conventional treatments involving steroids or immunosuppressive agents or anti-TNF therapy [166][167][168]. However, serious adverse effects accompanied HSC transplantation treatment [169][170][171][172], which triggered the attempts to employ allogeneic or autologous MSCs for Crohn's disease therapy. Early phase studies reported encouraging observations and autologous BM-MSC exhibited efficacy with improved Crohn's disease activity index scores [173][174][175][176].…”
Section: Mscs In Crohn's Diseasementioning
confidence: 99%